2014
DOI: 10.1021/jp4096776
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Modified Porous Graphene as Membrane for CO2/N2 Separation: Molecular Dynamic and First-Principles Simulations

Abstract: It is demonstrated that the fluorine-modified porous graphene membrane has excellent selectivity for CO2/N2 separation by using molecular dynamic (MD) simulations. We also investigated in detail the mechanism of the fluorine-modified porous graphene membrane for CO2/N2 separation by using first-principles simulations. We find that the diffusion barriers for CO2 and N2 to pass through the pore-22 (with 22 carbon atoms drilled out) graphene membrane are relatively small, which indicates that the pore-22 has a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 45 publications
(75 reference statements)
4
75
0
1
Order By: Relevance
“…These primarily electrostatic interactions have also been found in the Na-montmorillonite system [38]. To investigate the effect of the polarity of kerogen moieties on the extraction of the kerogen moieties with supercritical CO 2 , the dipole moments of the four molecules were calculated by the first-principle simulation; the details of the simulation have been reported in our previous work [50][51][52]. The dipole moments of [53,54].…”
Section: The Effect Of the Polarity Of Kerogen Moieties On Extractionmentioning
confidence: 85%
“…These primarily electrostatic interactions have also been found in the Na-montmorillonite system [38]. To investigate the effect of the polarity of kerogen moieties on the extraction of the kerogen moieties with supercritical CO 2 , the dipole moments of the four molecules were calculated by the first-principle simulation; the details of the simulation have been reported in our previous work [50][51][52]. The dipole moments of [53,54].…”
Section: The Effect Of the Polarity Of Kerogen Moieties On Extractionmentioning
confidence: 85%
“…The details of performance follow our previous work [3336]. Results show that dipole momentums of octadecane, phenol, and pyridine are 0.0322, 1.3059, and 2.2449 Debye, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…Beyond our studies, porous graphene has been widely explored by various computational approaches . It was shown that fluorine functionalization, water film and other surface modifications could enhance the selectivity of CO 2 .…”
Section: Ultrathin Membranesmentioning
confidence: 91%